Sex-Specificity of Oxidative Stress in Newborns Leading to a Personalized Antioxidant Nutritive Strategy - Jean-Claude Lavoie; André Tremblay (MDPI AG, 2018)
Oxidative stress is a critical process that triggers several diseases observed in premature infants. Growing recognition of the detriment of oxidative stress in newborns warrants the use of an antioxidant strategy that is likely to be nutritional in order to restore redox homeostasis. It appears essential to have a personalized approach that will take into account the age of gestation at birth and the sex of the infant. However, the link between sex and oxidative stress remains unclear. The aim of this study was to find a common denominator explaining the discrepancy between studies related to sex-specific effects of oxidative stress. Results highlight a specificity of sex in the levels of oxidative stress markers linked to the metabolism of glutathione, as measured in the intracellular compartments. Levels of all sex-dependent oxidative stress markers are greater and markers associated to a better antioxidant defense are lower in boys compared to girls during the neonatal period. This sex-specific discrepancy is likely to be related to estrogen metabolism, which is more active in baby-girls and promotes the activation of glutathione metabolism. Conclusion: our observations suggest that nutritive antioxidant strategies need to target glutathione metabolism and, therefore, should be personalized considering, among others, the sex specificity.